2016
DOI: 10.18511/0103-1716/rbcm.v24n3p103-111
|View full text |Cite
|
Sign up to set email alerts
|

Motivação para o Aumento da Massa Muscular em Praticantes de Exercício Resistido

Abstract: Nos últimos anos, houve um crescimento expressivo no número de academias de ginástica e musculação, bem como de pessoas matriculadas nas mesmas e, considerando o cenário mundial, o Brasil é um dos líderes nessa questão. O objetivo deste estudo foi analisar a motivação para o aumento da massa muscular em praticantes de exercício resistido e compará-la entre os sexos, as faixas etárias, o tempo de prática e a frequência semanal de prática dos participantes, bem como entre os objetivos que possuem com a mesma, e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…In a study with resistance training practitioners, also using the EAAT, women had a significantly higher score than men, which indicates that women have more dysfunctional eating attitudes than men (CLAUMANN et al, 2018). Another study that sought to evaluate the eating attitudes of university students using the EAT-26, also identified that women have more inappropriate eating attitudes, as did the present study.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…In a study with resistance training practitioners, also using the EAAT, women had a significantly higher score than men, which indicates that women have more dysfunctional eating attitudes than men (CLAUMANN et al, 2018). Another study that sought to evaluate the eating attitudes of university students using the EAT-26, also identified that women have more inappropriate eating attitudes, as did the present study.…”
Section: Resultssupporting
confidence: 65%
“…Other studies on the same topic also indicate that women have more dysfunctional eating attitudes than men, regardless of the instruments used to assess eating attitudes or behaviors (CARVALHO et al, 2013;CLAUMANN et al, 2018).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations